2019
DOI: 10.1002/hipo.23148
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive knowledge base of synaptic electrophysiology in the rodent hippocampal formation

Abstract: The cellular and synaptic architecture of the rodent hippocampus has been described in thousands of peer‐reviewed publications. However, no human‐ or machine‐readable public catalog of synaptic electrophysiology data exists for this or any other neural system. Harnessing state‐of‐the‐art information technology, we have developed a cloud‐based toolset for identifying empirical evidence from the scientific literature pertaining to synaptic electrophysiology, for extracting the experimental data of interest, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 100 publications
(136 reference statements)
1
18
0
Order By: Relevance
“…The previous version of Hippocampome.org included 122 hippocampal and entorhinal cortex cell types [ 22 ] classified according to the main neurotransmitter, axonal and dendritic patterns, synaptic specificity [ 44 ], molecular biomarkers [ 45 , 46 ], membrane biophysics, and firing patterns [ 47 ]. Moreover, this knowledge base also associates each identified neuron type with known information on potential connectivity [ 48 ] and synaptic signals [ 49 ]. While information about action-potential waveforms and neuronal burstiness may assist classification [ 50 52 ] and investigations of spike initiation mechanisms [ 53 ], the capability to disambiguate between cell types based on these features remained suboptimal [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The previous version of Hippocampome.org included 122 hippocampal and entorhinal cortex cell types [ 22 ] classified according to the main neurotransmitter, axonal and dendritic patterns, synaptic specificity [ 44 ], molecular biomarkers [ 45 , 46 ], membrane biophysics, and firing patterns [ 47 ]. Moreover, this knowledge base also associates each identified neuron type with known information on potential connectivity [ 48 ] and synaptic signals [ 49 ]. While information about action-potential waveforms and neuronal burstiness may assist classification [ 50 52 ] and investigations of spike initiation mechanisms [ 53 ], the capability to disambiguate between cell types based on these features remained suboptimal [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…where PSP exp (mV) and PSP model (mV) are the experimental and modeled PSPs amplitudes respectively and df = j E rev − V SS j (mV) is the driving force. For all the experiments we aimed to reproduce, E rev = − 8.5 mV was calculated for excitatory connections, while E rev = − 73 mV for inhibitory connections (Moradi & Ascoli, 2020). All simulations were run using the NEURON simulator as a core engine (Hines & Carnevale, 1997) with the Blue Brain Project's collection of hoc and NMODL (Hines & Carnevale, 2000) templates for parallel execution on supercomputers (Hines, Eichner, & Schürmann, 2008;Hines, Markram, & Schürmann, 2008).…”
Section: Stp Parameter Fittingmentioning
confidence: 99%
“…were directly obtained from the literature (see Supplementary Table S1 for AMPAR and GABAR rise and decay time constants, methods for NMDAR time constants, and Supplementary Table S2 for reversal potentials (Moradi & Ascoli, 2020)). In particular, for the τ decay ( Supplementary Table S1) with the exception of Maccaferri, Roberts, Szucs, Cottingham, and Somogyi (2000) who used either single or weighted biexponential fits, none of the other studies we considered explicitly reported how τ decay was extracted.…”
Section: Synaptic Model Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…This resource defines 122 neuron types based on their main neurotransmitter (glutamate or GABA) and the spatial distributions of their axons and dendrites (Wheeler et al, 2015). Hippocampome.org further annotates every neuron type with its reported connectivity (Rees et al, 2016), electrophysiological (Komendantov et al, 2019), molecular (White et al, 2020), synaptic (Moradi et al, 2020), morphological (Tecuatl et al, 2021), and functional (Sanchez-Aguilera et al, 2021) properties, in all cases providing links to the underlying experimental evidence. The ultimate goal of Hippocampome.org is to create biologically plausible computational models of the hippocampus (Venkadesh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%